2010
DOI: 10.1016/j.brainres.2010.07.088
|View full text |Cite
|
Sign up to set email alerts
|

Cyclothiazide induces seizure behavior in freely moving rats

Abstract: We have previously demonstrated that cyclothiazide (CTZ) is a potent convulsant drug inducing robust epileptiform activity in hippocampal neurons both in vitro and in vivo. Here we further establish an animal model for CTZ-induced behavioral seizures in freely moving rats. Microinjection of CTZ into left ventricle dose-dependently induced robust seizure behaviors within three hours after administration. At doses of 0.75 μmol, CTZ induced Racine score IV-V seizure behaviors in 71% (n=14) of the rats tested. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…Among them, 6 (46.2%) had been observed to have recurrent seizure behavior with the shortest latency of 15 days (mean latency of 76.3 ± 24.8 days) after CTZ injection; 4 of them were without recurrent seizure being observed (Figure 1(a)); and 4 other rats were dead at days 6, 9, 15, and 99 after the CTZ injection (including 1 that had generalized seizure one day before its death at day 15). Recurrent seizure behavior showed as blinking, salivating, facial or automatisms, forelimb clonus, and even rearing and falling, similar to those behaviors showed during the acute phase [12]. Among those 6 rats observed to have recurrent seizure behavior, we found 2 rats having multiple seizure episodes (4 and 3, resp.)…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Among them, 6 (46.2%) had been observed to have recurrent seizure behavior with the shortest latency of 15 days (mean latency of 76.3 ± 24.8 days) after CTZ injection; 4 of them were without recurrent seizure being observed (Figure 1(a)); and 4 other rats were dead at days 6, 9, 15, and 99 after the CTZ injection (including 1 that had generalized seizure one day before its death at day 15). Recurrent seizure behavior showed as blinking, salivating, facial or automatisms, forelimb clonus, and even rearing and falling, similar to those behaviors showed during the acute phase [12]. Among those 6 rats observed to have recurrent seizure behavior, we found 2 rats having multiple seizure episodes (4 and 3, resp.)…”
Section: Resultssupporting
confidence: 57%
“…CTZ has also been demonstrated to acutely induce seizure behavior and epileptic EEG in freely moving rats [12], which involves extrasynaptic GABAA receptor participation [13]. Thus, CTZ is thought to be a useful convulsant for seizure animal model generation.…”
Section: Introductionmentioning
confidence: 99%
“…Using this model, our results demonstrated that extrasynaptic GABA A Rs were downregulated by ~50% Recently, several studies have shown that CTZ is a potent convulsant capable of inducing epileptiform activity both in vivo and in cultured hippocampal neurons [16,17,25] , as well as evoking seizure behavior in freely-moving animals [26] . In the current study, we further extended this epilepsy model to hippocampal slices.…”
Section: Discussionmentioning
confidence: 90%
“…Besides epileptiform activity, we further studied whether THIP can directly modulate CTZ-induced seizure behavior in freely moving rats [38]. CTZ was injected repeatedly each day (0.25 μmol i.c.v.…”
Section: Resultsmentioning
confidence: 99%
“…CTZ induced seizure behavioral test was carried out similarly as previously reported [38]. Briefly, under general anesthetics with sodium pentobarbital (60 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%